1985
DOI: 10.1002/jhet.5570220322
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and spectral characterization of some new N‐substituted 2‐aminobenzothiazoles, 2‐aminothiazolopyridines and 2‐aminothiazoloquinolines

Abstract: A series of N‐substituted 2‐aminobenzothiazoles, 2‐aminothiazolopyridines, and 2‐aminothiazoloquinolines were prepared by the cyclization of N,N'‐disubstituted thiourea derivatives by bromine in acetic acid. The uv, ir and nmr data for these compounds are presented and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…Despite the results reported by Sarkis and Faisal [9], where the same method was used to prepare various thiazolopyridines, the formation of the pyridinium salts under the conditions used here was not surprising. A survey of the literature showed that similar pyridinium salts have been prepared by oxidative cyclization of unsubstituted pyridylthioureas with bromine in acetic acid, chloroform or methanol or with sulfuryl chloride in toluene [14,15].…”
Section: Resultscontrasting
confidence: 87%
See 1 more Smart Citation
“…Despite the results reported by Sarkis and Faisal [9], where the same method was used to prepare various thiazolopyridines, the formation of the pyridinium salts under the conditions used here was not surprising. A survey of the literature showed that similar pyridinium salts have been prepared by oxidative cyclization of unsubstituted pyridylthioureas with bromine in acetic acid, chloroform or methanol or with sulfuryl chloride in toluene [14,15].…”
Section: Resultscontrasting
confidence: 87%
“…The success of the reaction has been reported to depend upon the activation of the pyridine ring [7]. On the other hand, a two-step procedure was also described: a thiourea derivative was obtained from the reaction between an aminopyridine and an appropriate isothiocyanate which was subsequently cyclized by bromine in acetic acid or chloroform [9] (Scheme 1, Method B). If a halogen atom is present at the α position to the amino group, the cyclization occurs spontaneously [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…N ‐Benzoyl‐ N ′‐(2‐substituted quinolin‐4‐yl)thioureas [42] were cyclised by Hugerschoff reaction, [43] using bromine in acetic acid to form the corresponding 2‐benzamidothiazolo[5,4‐ c ]quinolines in 70–92 % yields (Scheme 8). [44] …”
Section: Synthesis Of Thiazoloquinolinesmentioning
confidence: 99%
“…8,9 Alternative methods for the syntheses of 4, 5, 6, and 7 substituted 2-aminobenzothiazoles employ phenylthioureas as the synthetic precursors (Scheme 1 C). In these cases, heterocycle ring formation can be carried out, albeit non regioselectively, by treating the phenylthioureas with bromine in chloroform10 or acetic acid 11. Alternatively, regiospecific cyclizations can be performed via S N Ar i reactions, employing phenylthioureas obtained from the appropriate ortho-fluoroanilines in the presence of sodium methoxide 12.…”
mentioning
confidence: 99%